The effect of a temporary product distribution channel on supply chain performance. (1st December 2016) - Khouja, Moutaz; Zhou, Jing
Abstract: We analyze a supply chain of a manufacturer and two retailers, a permanent retailer who always stocks the manufacturer's product and an intermittent deal‐of‐the day retailer who sells the manufacturer's product online for a short time. We find that without a deal‐of‐the‐day (DOTD) retailer, it is suboptimal for the manufacturer to offer a quantity discount while it is optimal for the retailer to offer periodic price discounts to consumers. With the addition of a DOTD retailer, it is likely to be optimal for the manufacturer to offer a quantity discount. We show that even without market expansion, i.e., no exclusive DOTD retailer consumers, opening the intermittent channel can leave the permanent retailer no worse‐off while increasing the manufacturer's profit. We identify the regular and discounted wholesale prices and the threshold quantity at which the manufacturer should give the discount. We also identify the optimal retail prices. We find that opening the intermittent channel increases the profit of the manufacturer, is likely to decrease the average retail price and to increase sales, and may increase the permanent retailer's profit. © 2016 Wiley Periodicals, Inc. Naval Research Logistics 63: 505–528, 2016